Genre in the music communication system and the artist’s mission - Serhaniuk, Liubov I.; Shapovalova, Liudmyla V.; Nikolaievska, Yuliia V.; Kopeliuk, Oleh O. (Linguistics and Culture Review, 2021)
The concept of the genre in the creative practice of the 20th century is defined as a complete historical cycle. The purpose of the study is to review theoretical ideas about the role of genre in the communicative system of musical culture of the 20th century through the criterion of cooperation of the composer and performer. A. Sokhor, V. Zuckerman, Ye. Nazaikinsky, I. Kohanyk et al. explained the essence of the genre from different standpoints, revealing the fundamentally open nature of the theory itself. However, there are ontological laws of the genre development. The first law is that music genre exists as a system of functions. The second law is that genre exists in social practice as a conditional model of developed musical archetypes that reflect deep mental structures of communication. These laws are illustrated with such examples as the genre of toccata for piano (Italian composer G. Petrassi and Ukrainian composer I. Karabits); the genre of ancient ballads in the repertoire of modern kobzars; chrono-articulatory foundations of the polyphonic cycle of V. Bibik "34 Preludes and Fugues. The Second Notebook", typical communication strategies in creative work of modern artists and performers.